2018
DOI: 10.1097/moo.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for evaluation and management of tongue-base obstruction in pediatric obstructive sleep apnea

Abstract: Purpose of review Tongue-base obstruction (TBO) is a common cause of persistent obstructive sleep apnea (OSA) after tonsillectomy and adenoidectomy in children. This review discusses available diagnostic modalities and surgical treatment options for the management of TBO. Recent findings Recently, a systematic review that included nine studies using drug-induced sleep endoscopy (DISE) in the evaluation of children with persistent OSA after tonsillectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Walker et al 17 also noted that the increased risk in these children was due to upper airway edema, but they did not specify a definitive cause or localization. And also, Ishman et al 18 implicated that in children who had just undergone tonsillectomy surgeries, tongue-based obstruction is an important cause of respiratory complications that occur after tonsillectomy surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al 17 also noted that the increased risk in these children was due to upper airway edema, but they did not specify a definitive cause or localization. And also, Ishman et al 18 implicated that in children who had just undergone tonsillectomy surgeries, tongue-based obstruction is an important cause of respiratory complications that occur after tonsillectomy surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 OSA represents an important comorbidity for this population, and hopefully the device will be approved by the FDA for children in the near future. 51 At present, previous OSA surgery seems to not represent a predictor of HNS response. Although a stratified analysis in the German Postmarket study revealed that a previous uvulopalatopharyngoplasty (UPPP) is associated with higher risk of being non-responders, 43 but as more patients have been included this tendency has not been observed.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 91%
“…We also recognize that HGNS is not the only mechanism available to treat OSA attributable to tongue base collapse in the pediatric population. Such children also can be considered for lingual tonsillectomy, posterior midline glossectomy, tongue suspension suture, epiglottopexy, tongue‐lip adhesion, and hyoid suspension 8 …”
Section: Discussionmentioning
confidence: 99%
“…Such children also can be considered for lingual tonsillectomy, posterior midline glossectomy, tongue suspension suture, epiglottopexy, tongue-lip adhesion, and hyoid suspension. 8…”
Section: Discussionmentioning
confidence: 99%